Differentiating conceptual modelling from data modelling, knowledge modelling and ontology modelling and a notation for ontology modelling - Dillon, Tharam S.; Chang, Elizabeth; Hadzic, Maja; Wongthongtham, Pornpit (CRPIT, Australasian Computer Science, 2008)
This paper considers conceptual modelling for three purposes namely data modelling, knowledge modelling and ontology modelling. It differentiates between the nature of the conceptual models for these three. It then proposes a representation suitable for ontology modelling.